Cancerogenic parasites in veterinary medicine: a narrative literature review - Niccolò Fonti; Francesca Parisi; Francesca Mancianti; Giulia Freer; Alessandro Poli (Infectious Agents and Cancer, 2023)
Abstract Parasite infection is one of the many environmental factors that can significantly contribute to carcinogenesis and is already known to be associated with a variety of malignancies in both human and veterinary medicine. However, the actual number of cancerogenic parasites and their relationship to tumor development is far from being fully understood, especially in veterinary medicine. Thus, the aim of this review is to investigate parasite-related cancers in domestic and wild animals and their burden in veterinary oncology. Spontaneous neoplasia with ascertained or putative parasite etiology in domestic and wild animals will be reviewed, and the multifarious mechanisms of protozoan and metazoan cancer induction will be discussed.